2017
DOI: 10.3389/fpls.2017.01683
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz Proteinase Inhibitors Limit Water Stress Responses in White Clover (Trifolium repens L.) Plants

Abstract: The response of plants to water deficiency or drought is a complex process, the perception of which is triggered at the molecular level before any visible morphological responses are detected. It was found that different groups of plant proteinase inhibitors (PIs) are induced and play an active role during abiotic stress conditions such as drought. Our previous work with the white clover (Trifolium repens L.) Kunitz Proteinase Inhibitor (Tr-KPI) gene family showed that Tr-KPIs are differentially regulated to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 110 publications
0
19
0
1
Order By: Relevance
“…The authors, however, concluded that HvPap1 and HvPap19 are drought-inducible genes and may cause differential effects on barley plants subjected to drought (Gomez-sanchez et al, 2019). Islam et al (2017) investigated the functions of Kunitz proteinase inhibitors (KPIs) in white clover (Trifolium repens L.) plants subjected to water deficits using several knockdown lines of different Tr-KPIs. The study utilised two distinct water withholding regimes, a Non-PreStress treatment with direct exposure of plants to water deficits and a PreStress treatment in which plants were initially exposed to drought stress and rehydration, followed by a final drought stress treatment.…”
Section: Using Knockout or Knockdown Mutant Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors, however, concluded that HvPap1 and HvPap19 are drought-inducible genes and may cause differential effects on barley plants subjected to drought (Gomez-sanchez et al, 2019). Islam et al (2017) investigated the functions of Kunitz proteinase inhibitors (KPIs) in white clover (Trifolium repens L.) plants subjected to water deficits using several knockdown lines of different Tr-KPIs. The study utilised two distinct water withholding regimes, a Non-PreStress treatment with direct exposure of plants to water deficits and a PreStress treatment in which plants were initially exposed to drought stress and rehydration, followed by a final drought stress treatment.…”
Section: Using Knockout or Knockdown Mutant Linesmentioning
confidence: 99%
“…For example, Gomez-sanchez et al (2019) suggested that the observed unexpected increase in cuticle thickness of KDPap1, an HvPap1 knockdown mutant line, could have been due to pleiotropic effects associated with the knocked-down cysteine protease gene. In addition, knockdown mutants exhibit some residual mRNA expression or protein accumulation of the knocked-down gene to varying extents (Islam et al, 2017;Gomezsanchez et al, 2019;Mishra et al, 2021), hence the knockdown character (Gomez-sanchez et al, 2019). For example, while Mishra et al (2021) reported a 99% reduction in the transcript expression of the target AtFtsHi3 gene in the generated knockdown mutant, ftshi3-I (kd), relative to the wild-type, other studies reported much lower reduction rates of the target genes (Islam et al, 2017).…”
Section: Overall Functions: More Than Just Acts Of Protein Degradatio...mentioning
confidence: 99%
“…Cluster 1 was the largest group with 427 DEGs induced under both water shortage treatments. The most representative biological processes identified with GO term enriched analysis (p < 0.05) in this cluster comprised, among others, "response to water deprivation" (GO0009414), "negative regulation of endopeptidase activity" (GO0010951), "glutathione metabolic process" (GO0006749), "response to wounding" (GO0009611), "sodium ion transport" (GO0006814), and "serine-type endopeptidase inhibitor activity" (GO0004867), which have been extensively associated with both biotic and abiotic stress [59,60]. In particular, serine protease inhibitors play an important role in cell survival, development, and host defense, i.e., transgenic Arabidopsis thaliana plants overexpressing serine protease inhibitors showed higher RWC, reduced lipid peroxidation, and enhanced activity of antioxidant glutathione-S-transferase [61].…”
Section: Validation Of the Microarraymentioning
confidence: 99%
“…The KNIs belong to a β‐trefoil fold superfamily with high loop plasticity and an approximate molecular mass of 21 kDa. The β‐trefoil fold also has two disulfide bridges to inhibit a wide range of proteinases . This suggests that KNIs could act as proteinase regulators in plant germination and in a defense response during insect attack .…”
Section: Introductionmentioning
confidence: 99%
“…The -trefoil fold also has two disulfide bridges to inhibit a wide range of proteinases. 22 This suggests that KNIs could act as proteinase regulators in plant germination and in a defense response during insect attack. [23][24][25][26] Recent evidence also suggests that KNIs are involved in programmed cell death, growth, and development in plants.…”
Section: Introductionmentioning
confidence: 99%